Case Report: A case of toothache of cardiac origin with a long-term clinical course - Maeda, Chizuko; Suga, Takayuki; Oishi, Kiyotoshi; Toyofuku, Akira (Frontiers in Pain Research, 2025)
BackgroundToothache of cardiac origin is a rare but significant form of referred pain originating from cardiac pathology such as angina pectoris. Although jaw and throat discomfort are known referred pain sites, toothache alone is an uncommon presentation. Misdiagnosis often leads to unnecessary dental interventions and delays in appropriate cardiac treatment, highlighting the need for greater awareness among both dentists and internists.Case presentationA 76-year-old woman presented with persistent pain in the gingiva around teeth #33 and #34, accompanied by sharp chest discomfort which would subside in about 5–6 min. Extensive dental examinations, including extractions, failed to resolve her symptoms. Initial cardiac evaluations—electrocardiogram, Holter monitoring, echocardiography, and chest computed tomography—were unremarkable. Consequently, she was diagnosed with atypical odontalgia and prescribed antidepressants, but these proved ineffective. However, over several months, the toothache worsened upon exertion, accompanied by chest pain unresponsive to standard analgesics. A specialized cardiac imaging center finally detected severe stenosis (90%–99%) of the left anterior descending artery and Right Coronary Artery, as well as a left ventricular thrombus. Coronary angiography confirmed unstable angina, and the patient underwent a Dor procedure to remove the thrombus alongside coronary artery bypass grafting. Following surgery, her toothache and chest pain completely resolved.ConclusionThis case features a protracted course from symptom onset to definitive treatment. In older patients reporting persistent tooth or gingival pain with intermittent chest discomfort—especially when symptoms are exertional and dental findings are negative—clinicians should consider a cardiac origin and expedite cardiologic imaging to avert hazardous delays. Systematic accumulation of cases and cross-disciplinary research are essential to establish actionable diagnostic guidance and move beyond anecdotal evidence.